1998
DOI: 10.1002/(sici)1098-108x(199809)24:2<167::aid-eat6>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

The significance of body size estimation in eating disorders: Its relationship with clinical and psychological variables

Abstract: Objective To assess the relationship between body size estimation on the one hand and clinical and psychological variables on the other. Method: Body size estimation was tested with the video distortion method on a life‐size screen in normal women (n = 45) and compared to a total of 189 female eating disorder patients (100 with restricting anorexia nervosa, 41 with binging/purging anorexia nervosa, 48 with bulimia nervosa). The subjects' cognitive responses (what they think they really look like), affective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1
6

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 19 publications
0
16
1
6
Order By: Relevance
“…body dimensions. 6,40 Participants could correct the degree of distortion of the photo as often as they wanted. They were instructed to confirm their choice by pressing the ''Enter'' key when they thought that the current adjustment represented the best answer to the question.…”
Section: Photo Distortion Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…body dimensions. 6,40 Participants could correct the degree of distortion of the photo as often as they wanted. They were instructed to confirm their choice by pressing the ''Enter'' key when they thought that the current adjustment represented the best answer to the question.…”
Section: Photo Distortion Techniquementioning
confidence: 99%
“…[1][2][3] Body image disturbances can be differentiated into three components, 4,5 which seem to be only modestly intercorrelated. 6 The cognitive-affective component reflects the patients' thoughts and feelings about their own body. For example, it has been shown that women with eating disorders display negative emotions and cognitions to a greater extent when looking at their own bodies than do healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The second is emotional, how an individual "feels" he or she looks. Last is idealistic, how an individual "wants" to look [1] . All three dimensions can different at any given point in time.…”
Section: Introductionmentioning
confidence: 99%
“…A distorção da percepção associada à inanição 16 e a comorbidade com a depressão são bem conhecidas, assim como o impacto dessas sobre a competência 17 . No entanto, há muitos outros fatores que devem ser levados em conta quando é julgada a competência em pacientes com AN 16,17 .…”
Section: Artigo Originalunclassified
“…No entanto, há muitos outros fatores que devem ser levados em conta quando é julgada a competência em pacientes com AN 16,17 .…”
Section: Artigo Originalunclassified